Polarization Energies from Efficient Representation of the Linear Density–Density Response Function. Issue 4 (20th January 2021) - Dreßler, Christian; Sebastiani, Daniel
Abstract: The authors present a proof‐of‐concept study for the calculation of atomic forces on a solvated molecule by means of the linear density–density response function in its moment expanded representation. The density–density response function represents an efficient way to compute molecular forces for arbitrary external potentials via an ab initio scheme, without the need to perform an explicit self‐consistent quantum chemical calculation for each configuration of the chemical environment. Here, the authors show that it is indeed possible to determine the atomic forces of interacting bulk‐like molecular complexes due to polarization effects of the surrounding molecules with good accuracy. This study represents a significant step the practical applicability of the approach, which is still in a development phase. The potential application of the computational scheme in terms of molecular dynamics simulations is illustrated by considering a variety of cluster conformations, as they would be found within a molecular dynamics trajectory. Abstract : An efficient representation of the static linear density–density response function is used in this work to calculate molecular polarization energies due to surrounding molecules. The potential application in terms of molecular dynamics simulations is illustrated by considering a variety of cluster conformations of formaldehyde, as they would be found within a molecular dynamics trajectory.